Dietary Magnesium Intake and Risk of Type 2 Diabetes Mellitus Using Data from the HEALTHY Study. (29th May 2020) - Naseeb, Manal; Bruneau, Michael L.; Milliron, Brandy-Joe; Sukumar, Deeptha; Foster, Gary D; Smith, Sinclair A; Volpe, Stella
Abstract: Objectives: Type 2 diabetes mellitus (T2DM) in children and adolescents has increased dramatically worldwide. Diet plays a key role in the development of T2DM, but little is known about the contribution of dietary magnesium intake in the risk of T2DM among children and adolescents. We conducted secondary analyses using the HEALTHY Study data. The HEALTHY Study was a multi-component, school-based intervention designed to reduce modifiable risk factors for T2DM in middle school students from 6 th through 8 th grades. The purpose of our study was to examine whether the difference in dietary magnesium intake, body mass index (BMI) percentile, and plasma glucose and insulin concentrations from 6 th to 8 th grade were related in the intervention schools and in the control schools that participated in the HEALTHY Study. Methods: A total of 2181 students from intervention and control schools with completed dietary records, BMI percentile, plasma glucose and insulin concentrations, at 6 th and 8 th grades were included in these analyses. Dietary magnesium intake was self-reported using the Block Kids Food Frequency Questionnaire. A hierarchical multiple regression model was used to determine whether the difference in dietary magnesium intake, BMI percentile, and plasma glucose and plasma insulin concentrations from 6 th to 8 th grades were related, while adjusting for dietary calcium intake. Results: The difference in dietary magnesium intake was a significant predictor for changes in BMI percentile in control schools from 6 th to 8 th grade (β = −0.07, 95% confidence interval [CI] = −0.03 to −0.01, P  = 0.007; R 2 [regression coefficient effect size] = 0.24, 95% CI for R 2  = 0.19 to 0.28) indicating a small-to-medium effect size. Conclusions: We concluded that changes in dietary magnesium intake from 6th to 8th grades were negatively related to changes in BMI percentile among middle school students. Funding Sources: The original research related to this abstract was funded by the National Institute of Diabetes and Digestive and Kidney Disease (NIDDK) of the National Institutes of Health (NIH), with additional support from the American Diabetes Association.